Answer:
24+24x I believe is the answer. Good luck on your test :)
Answer:
25
Step-by-step explanation:
Don't ask
Answer:
The function f(x) when x=x-4 is
or ![f(x-4)=3x(x-8)+53](https://tex.z-dn.net/?f=f%28x-4%29%3D3x%28x-8%29%2B53)
Step-by-step explanation:
Given function f is defined by ![f(x)=3x^2+5](https://tex.z-dn.net/?f=f%28x%29%3D3x%5E2%2B5)
Now to find the function f(x-4):
![f(x)=3x^2+5](https://tex.z-dn.net/?f=f%28x%29%3D3x%5E2%2B5)
Put x=x-4 in the above function we get
![f(x-4)=3(x-4)^2+5](https://tex.z-dn.net/?f=f%28x-4%29%3D3%28x-4%29%5E2%2B5)
(using the formula
)
![f(x-4)=3(x^2-8x+16)+5](https://tex.z-dn.net/?f=f%28x-4%29%3D3%28x%5E2-8x%2B16%29%2B5)
(adding the like terms)
![f(x-4)=3x^2-24x+53](https://tex.z-dn.net/?f=f%28x-4%29%3D3x%5E2-24x%2B53)
![f(x-4)=3x(x-8)+53](https://tex.z-dn.net/?f=f%28x-4%29%3D3x%28x-8%29%2B53)
Therefore
or ![f(x-4)=3x(x-8)+53](https://tex.z-dn.net/?f=f%28x-4%29%3D3x%28x-8%29%2B53)
The function f(x) when x=x-4 is
or ![f(x-4)=3x(x-8)+53](https://tex.z-dn.net/?f=f%28x-4%29%3D3x%28x-8%29%2B53)